2014
DOI: 10.1080/14681994.2014.939506
|View full text |Cite
|
Sign up to set email alerts
|

Relationships and sexual expression in later life: a biopsychosocial perspective

Abstract: The literature on sexual activity and ageing has grown substantially in the past 20 years. Until recently, a medicalized perspective dominated. In the past decade research based on a social-relational perspective has emerged. We summarize recent work from both perspectives. In addition to the effects of disease on sexual functioning of men and women over the age of 50, this review emphasizes sexual expression among older couples, newly emerging topics such as human immunodeficiency virus (HIV) in the older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 58 publications
2
49
0
1
Order By: Relevance
“…More specifically, pronatalist and youth oriented conceptions of sexuality pervasively perpetuated by the media appear to influence older women more than older men, namely because women experience menopause at around age 51 whilst men remain fertile until later life stages (Alterovits & Mendelsohn, 2009;Baker, 2005;DeLamater & Koepsel, 2015;Kenny, 2013;Vares, 2009). Attitudes toward sexuality and aging seem to reflect and endorse a largely -youth-oriented‖ Western culture.…”
Section: Sex As a Privilege Of The Young And Beautifulmentioning
confidence: 99%
“…More specifically, pronatalist and youth oriented conceptions of sexuality pervasively perpetuated by the media appear to influence older women more than older men, namely because women experience menopause at around age 51 whilst men remain fertile until later life stages (Alterovits & Mendelsohn, 2009;Baker, 2005;DeLamater & Koepsel, 2015;Kenny, 2013;Vares, 2009). Attitudes toward sexuality and aging seem to reflect and endorse a largely -youth-oriented‖ Western culture.…”
Section: Sex As a Privilege Of The Young And Beautifulmentioning
confidence: 99%
“…В первую очередь, этот подход используется в обла-сти психического здоровья, в анализе интернализа-ции социальных проблем и в теории развития [2]; при работе с хроническими болевыми состояниями в онкологии и неврологии [3][4][5], со старением и тер-минальными состояниями [6,7], собственно в психи-атрии, психотерапии и психореабилитации [8,9], в работе с инвалидизирующими состояниями [10], с нарушением пищевого поведения [11] и так далее.…”
Section: содержание понятияunclassified
“…This makes women, despite legitimizing their relationships in marriage, to be in conflict with their sexual assertiveness or lack of it. Researches on self-expression revealed that when people trust each other and express their thoughts and feelings, they may develop an intimate relationship and this improves the sexual intimacy of couples and help them enjoy their sexual relationship more (21).…”
Section: Discussionmentioning
confidence: 99%